" . . . A Right Good People" - Warren, Harold (Appalachian State University, 1974)
A collection of true stories gathered from the Southern Appalachian people, this book echoes the folkways and values of another era. Published in 1974, the stories collected in "... A Right Good People" were originally published in the ###Charlotte Observer,# the largest newspaper in the Carolinas in the 1970s. These stories were written with the intention of illustrating the heritage of the Appalachian people and letting them speak about their culture and traditions for themselves.